IMPORTANCE OF IRRIGATION OF PLANTS USING NEW MATERIALS IN DESERT AREAS (Intent Research Scientific Journal, 2023)
Desert areas pose significant challenges for plant growth due to their arid and water-deficient environments. Proper irrigation methods are crucial to sustain plant life in these regions. This scientific paper investigates the importance of employing new materials in irrigation systems to enhance water retention and delivery efficiency. The study reviews existing literature on desert irrigation techniques and evaluates the potential benefits of using novel materials. A novel irrigation methodology is proposed, and its effectiveness in promoting plant growth and conserving water is examined. The results demonstrate that the adoption of new materials in desert area irrigation holds great promise for sustainable agriculture and ecosystem restoration.